Interrupted Sampling Repeater Jamming Recognition Method Based on Wavelet Packet Transform - Zhong Qi; Fan Shoutao; He Zhiyi; Liu Jianxin (IEEE Access)
The radar jammers operating in an interrupted sampling repeater jamming (ISRJ) mode can intercept transmitted signal, modulate the intercepted signal slices, and retransmit them back to the radar receiver to create coherent interference. This interference can generate false target groups at the receiving end, significantly disrupting the detection and recognition of targets. To address this issue, we propose a method for interference and target recognition based on the difference in the coefficient of variation obtained from wavelet packet transforms of jamming and target echoes, which can effectively eliminate the impact of ISRJ attacks. In the proposed method, after performing target detection on the received signals to obtain distance information of potential targets and interference, the received signals are up-converted to an intermediate frequency, and wavelet packet transforms are applied to the up-converted signals at locations of potential targets and interference to obtain the corresponding wavelet packet transform coefficients’ coefficient of variation (WPTCCV). Since the WPTCCV for targets is smaller than that for interference, the interference can be identified by comparing the obtained WPTCCV with a defined threshold. Simulation results demonstrate that the proposed method exhibits good recognition performance for the false targets generated by interrupted sampling repeater jamming.